Gender and Occupation in Digital Marketing: How Consumers Perceive Promotion Mix For English Certification Programs - Khairiyah Kamilah; Fandawa Saputra; Retnaningsih (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The increasing demand for English certification programs has led educational institutions to refine their digital marketing strategies to reach potential candidates effectively. However, demographic factors, such as gender and occupation, significantly influence how consumers perceive and engage in promotional content. Understanding these differences is crucial for designing targeted and effective marketing strategies in the educational sector.Purpose: This study examines how gender and occupation influence respondents' perceptions of the promotion mix for an English certification program, the preferred channel for discovering certification events, and their motivation for enrolling. The research particularly explores preferences in social media usage, word-of-mouth recommendations, interactivity in official accounts, soft versus hard selling content, and the effectiveness of ads across different platforms.Design/methodology/approach: A quantitative research design was employed with 500 respondents (250 male and 250 female) from different occupational backgrounds: students, freelancers, job seekers, and professionals. Data were analyzed using Multivariate Analysis of Variance (MANOVA) to simultaneously assess the influence of gender and occupation on multiple dependent variables. Normality tests confirmed that the data met the assumptions of MANOVA analysis.Findings/Result: The results reveal the following: Gender significantly influenced respondents’ preference for word-of-mouth recommendations (p2) and interactive official accounts (p3), with females showing higher engagement in both; Occupation significantly affects social media preference (p1), promotional content style (p4), and the preferred channel for event discovery, with students and job seekers favoring Instagram/TikTok, whereas professionals rely more on LinkedIn and email marketing; Interaction effects (gender × occupation) were significant for preference for interactive official accounts, particularly among female students and female job seekers; No significant differences were found in ad placement preferences (p5) across gender and occupation groups.Conclusion: This study highlights that gender and occupation are key determinants of digital marketing effectiveness in English certification programs. Marketing strategies should be tailored to demographic segments, with peer-driven promotions and interactive content appealing more to female audiences, while channel selection and content style should be aligned with occupational preferences.Originality/value (State of the art): This study contributes to the digital marketing and education industry by providing empirical evidence on how demographic factors influence the effectiveness of promotion mix strategies. Unlike previous studies that focus solely on gender or occupation, this study examines their combined effects using MANOVA analysis, offering a more comprehensive understanding of consumer preferences in education marketing. These findings provide practical insights for marketers to develop more personalized and data-driven promotional strategies for online courses and certification programs. Keywords: digital marketing, promotion mix, social media advertising, consumer behavior, english certification, gender differences